The Role of Metacognition, Metamemory and Meta-emotion in Predicting Students' Self-directed Learning - Mahsa Alamolhoda (Islamic Azad University, Tabriz Branch, 2021)
The aim of this research was determine the role of metacognition, metamemory and meta-emotion in predicting students' self-directed learning. The research method was cross-sectional from type of correlation. The research population was all high school students of Urmia city in the 2019-2020 academic years. The research sample was 400 students who were selected by multi-stage cluster sampling method. The research tools were the O'Neill & Abedi metacognition inventory (1996), Troyer & Rich metamemory questionnaire (2002), Mitmansgruber & et al meta-emotion questionnaire (2009) and Fisher & et al self-directed learning scale (2001). Data were analyzed by Pearson correlation coefficient and multiple regression with enter model methods in SPSS-19 software. The findings showed that metacognition, metamemory and positive meta-emotion had a positive and significant relationship with self-directed learning and negative meta-emotion had a negative and significant relationship with self-directed learning. Also, the variables of metacognition, metamemory and meta-emotion significantly could predicted 40.8 percent of variance of students' self-directed learning and in this predicting the role of metamemory was higher than other variables (p < 0.01). According to the results of the present study, to improve students' self-directed learning, can be designed programs to increase metacognition, metamemory and positive meta-emotion and decrease negative meta-emotion and implement them through workshops.